Are heat waves susceptible to mitigate the expansion of a species progressing with global warming?. Issue 9 (30th July 2013) - Robinet, Christelle; Rousselet, Jérôme; Pineau, Patrick; Miard, Florie; Roques, Alain
Abstract A number of organisms, especially insects, are extending their range in response of the increasing trend of warmer temperatures. However, the effects of more frequent climatic anomalies on these species are not clearly known. The pine processionary moth, Thaumetopoea pityocampa, is a forest pest that is currently extending its geographical distribution in Europe in response to climate warming. However, its population density largely decreased in its northern expansion range (near Paris, France) the year following the 2003 heat wave. In this study, we tested whether the 2003 heat wave could have killed a large part of egg masses. First, the local heat wave intensity was determined. Then, an outdoor experiment was conducted to measure the deviation between the temperatures recorded by weather stations and those observed within sun‐exposed egg masses. A second experiment was conducted under laboratory conditions to simulate heat wave conditions (with night/day temperatures of 20/32°C and 20/40°C compared to the control treatment 13/20°C) and measure the potential effects of this heat wave on egg masses. No effects were noticed on egg development. Then, larvae hatched from these egg masses were reared under mild conditions until the third instar and no delayed effects on the development of larvae were found. Instead of eggs, the 2003 heat wave had probably affected directly or indirectly the young larvae that were already hatched when it occurred. Our results suggest that the effects of extreme climatic anomalies occurring over narrow time windows are difficult to determine because they strongly depend on the life stage of the species exposed to these anomalies. However, these effects could potentially reduce or enhance the average warming effects. As extreme weather conditions are predicted to become more frequent in the future, it is necessary to disentangle the effects of the warming trend from the effects of climatic anomalies when predicting the response of a species to climate change.